Heart rate profiles and energy cost of locomotion during cross-country skiing races - Mognoni, P.; Rossi, G.; Gastaldelli, F.; Canclini, A.; Cotelli, F. (European Journal of Applied Physiology, 2001)
The purpose of this study was to compare heart rate responses and speed in two cross-country skiing races, which were run by seven male and seven female subjects by using classic and free style. Heart rates and skiing velocities were analyzed over flat, uphill and downhill sections, which were run from one to three times. Heart rates were higher in uphill sections than in flat sections; a steady-state heart rate was never reached in the downhill section. When the same uphill section was repeated, the heart rate tended to increase but the speed to decrease. Oxygen uptake (VO2) was calculated from heart rate:VO2 ratio, measured during uphill walking with the aid of poles. The mean (SD) energy cost of locomotion (i.e., the ratio between net VO2 and speed) was 162.1 (9.4) ml·km-1·kg-1 and 147.7 (7.1) ml·km-1·kg-1when male subjects ran the flat section after first downhill by using classic and free style, respectively. Females had lower values for VO2 and speed, but similar energy costs. In general, the variability of the energy cost of locomotion in skiers of a similar competitive level is of the same order as that found in uphill walking on a treadmill.